Flexible, Piezoelectric Aluminum-Doped Zinc Oxide Energy Harvesters with Printed Electrodes for Wearable Applications - Suhaimi, Muhammad I.; Nordin, Anis Nurashikin; Md Ralib, Aliza Aini; Lim, Lai Ming; Samsudin, Zambri (International Journal of Sensors Wireless Communications and Control, 2022)
Aims: Recent advancements in sensing technology and wireless communications have accelerated the development of the Internet of Things (IoT) which promotes the usage of wearable sensors. An emerging trend is to develop self-sustainable wearable devices, thus eliminating the necessity of the user to carry bulky batteries. In this work, the development of a flexible piezoelectric energy harvester that is capable of harvesting energy from low frequency vibrations is presented. The target application of this energy harvester is for usage in smart shoes. Objectives: The objective of this research is to design, fabricate and test an energy harvester on PET substrate using Aluminum Zinc Oxide as its piezoelectric layer. Methods: The energy harvester was designed as a cantilever structure using PET/AZO/Ag layers in d33 mode which can generate large output voltages with small displacements. The electrodes were designed as an interdigitated structure in which two significant design parameters were chosen, namely the effect of gap between electrodes, g and number of inter-digital electrodes (IDE) pairs, N to the output voltage and resonant frequency. Results: The sputtered AZO on PET showed c-axis orientation at 002 peak with 2 values of 34.45° which indicates piezoelectric behavior. The silver IDE pairs were screen-printed on the AZO thin film. Functionality of the device as an energy harvester was demonstrated by testing it, using a shaker. The energy harvester was capable of generating 0.867 Vrms output voltage when actuated at 49.6 Hz vibrations. Conclusion: This indicates that the AZO thin films with printed silver electrodes can be used as flexible, d33 energy harvesters.
Keywords: piezoelectric